Dithiolodithiole as a Building Block for Conjugated Materials1. (28th April 2014) - Schipper, Derek J.; Moh, Lionel C. H.; Müller, Peter; Swager, Timothy M.
Abstract The development of new conjugated organic materials for dyes, sensors, imaging, and flexible light emitting diodes, field‐effect transistors, and photovoltaics has largely relied upon assembling π‐conjugated molecules and polymers from a limited number of building blocks. The use of the dithiolodithiole heterocycle as a conjugated building block for organic materials is described. The resulting materials exhibit complimentary properties to widely used thiophene analogues, such as stronger donor characteristics, high crystallinity, and a decreased HOMO–LUMO gap. The dithiolodithiole (C4S4) motif is readily synthetically accessible using catalytic processes, and both the molecular and bulk properties of materials based on this building block can be tuned by judicious choice of substituents.